Fact and fable in psychology - Jastrow, Joseph, 1863-1944. (Boston and New York, Houghton, Mifflin and Co., 1900)
"The present collection of essays is offered as a contribution towards the realization of a sounder interest in and a more intimate appreciation of certain problems upon which psychology has an authoritative charge to make to the public jury. These essays take their stand distinctively upon one side of certain issues, and as determinately as the situation seems to warrant, antagonize contrary positions; they aim to oppose certain tendencies and to support others; to show that the sound and profitable interest in mental life is in the usual and normal, and that the resolute pursuit of this interest necessarily results in bringing the apparently irregular phenomena of the mental world within the field of illumination of the more familiar and the law-abiding. They further aim to illustrate that misconceptions in psychology, as in other realms, are as often the result of bad logic as of defective observation, and that both are apt to be called into being by inherent mental prepossessions. Some of the essays are more especially occupied with an analysis of the defective logic which lends plausibility to and induces credence in certain beliefs; others bring forward contributions to an understanding of phenomena about which misconception is likely to arise; still others are presented as psychological investigations which, it is believed, command a somewhat general interest"--Preface. (PsycINFO Database Record (c) 2005 APA, all rights reserved)
Preface.--The modern occult.--The problems of psychical research.--The logic of mental telegraphy.--The psychology of deception.--The psychology of spiritualism.--Hypnotism and its antecedents.--The natural history of analogy.--The mind's eye.--Mental prepossession and inertia.--A study of involuntary movements.--The dreams of the blind.--Index.
Microfilmed for preservation.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Includes bibliographical references and index.
Keywords: Parapsychology; Occultism; Hypnotism; Hypnosis; Occultism; Parapsychology; Hypnotism; Occultism; Parapsychology; Electronic books